The Effect of Discovery learning Model Assisted by Evolution Video on Concept Mastery and Science Literacy in High School Students - Jamallika, Sa'adah Nurwidyani; Handziko, M.Pd., Rio Christy; Krisnawati, Titik (JURNAL PENDIDIKAN SAINS (JPS), 2024)
The objective of this research is to examine the impact of the Discovery learning model, supplemented by evolution films, on concept mastery and scientific literacy in the classroom. This study involved class XII students from SMA Negeri 1 Ngaglik, Sleman Yogyakarta. The research sample was determined using a purposive sampling technique, yielding two classes: 1 class as the control class and the other as the experimental class. The data was collected using a pretest, posttest, and final assessment. Data was analyzed using SPSS 27. The research results show that the value of Asymp. Sig. (2-tailed) from the Mann-whitney test, mastery of experimental class concepts was <0.001 (p<0.05) and scientific literacy was 0.032 (p<0.05), indicating that the application of the discovery learning model assisted by evolutionary videos had an effect on increasing the mastery concepts and scientific literacy of students at Ngaglik 1 State High School.